The Study on Language Meaning and Its Ambiguities in Building Human Language Communication - Marsuki; Chindy Hanggara Rosa Indah (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2024)
Semantics is one of the linguistic branches which studies language meaning scientifically. The scopes of semantics come from two major sources, namely linguistics and philosophy which have attempted to explain meaning in natural language into three main ways, namely words, sentence and act of communication. The article is intended to describe meaning in language and its ambiguities in building human language communication. Based on the data analysis, it is found that the language meaning in building human language communication covers minimal unit of meaning and ambiguities. The minimal unit of meaning means the minimal sound of meaning which involves word or morphemes in morphology. Sentence is also including the smallest unit of meaning in syntax, while proposition and utterance belong to the minimal unit of meaning in semantics and pragmatics consecutively. Besides, the language meaning interpretation in language communication is traced by the ambiguity which means a pair of expression which has the same form but different interpretation in meaning. In this case, the ambiguity is grouped into lexical ambiguity and structural ambiguity.